Determining the effective factors on voluntary childlessness and one-child tendency from couples' perspective: Compulsory(Involuntary) childlessness or one-child or child-avoidance (child-free)? - Neda Ahmadzadeh tori; Hamid Sharif Nia; Fatemeh Ghaffari; Fereshteh Behmanesh; Abolghasem Pourreza (Babol University of Medical Sciences, 2023)
Background: Couples' childless and one-child intention is one of the crucial challenges in all societies. Considering the aging of the world's population and the need to review birth control policies, it is necessary to take evidence-based measures. Therefore, the present study aimed to investigate the influencing factors on the tendency of couples to be childless and have only one child. Methods: The present study is the first part of a mixed (qualitative-quantitative) study. The study is qualitative with a conventional content analysis approach. The research population consists of all couples aged 15-49 in 2021 in Babol city, who were single or childless and had no intention of pregnancy in the future. Sampling is based on the purpose, and the number of samples is 40 couples. To collect data, face-to-face and semi-structured interviews were conducted with the participants. Sampling continued until data saturation. The data were analyzed by the conventional content analysis method. Results: The results of the analysis include 140 codes, 30 sub-categories, 9 categories (family economic problems, uncertainty in the future security of the child, threatened priorities, uncertainty about the continuation of life, Fear of becoming a parent, lack or weakness of support, diminishing religious beliefs, social role modeling and negative experiences of childbearing) and two themes (individual limitations and social limitations). These factors indicate the mandatory conditions for childlessness or one-child choice or voluntary child-free. Conclusion: The results revealed that voluntary childlessness and single-child depend on various individual and social aspects. Some of these factors have made couples choose a childless or one-child lifestyle against their will and under forced circumstances. Financial support and welfare of the government, parenting education and efforts to change the attitude of couples towards having children by the government can help to maintain and improve the health of the family and achieve the goals of encouraging population growth policies.